Airline Legal Liability for Lost Cabin Baggage: A Review of Consumer Protection in Air Transportation - Wibowo, Evan Fernando Agung; Sudiro, Amad (Jurnal Ilmu Hukum Kyadiren, 2025)
This study examines the legal liability of airlines for the loss of passengers’ belongings stored in cabin baggage—an issue that frequently arises yet remains largely overlooked by current legal frameworks. In contrast to checked baggage, cabin baggage remains under the direct supervision of passengers, leading airlines to often deny responsibility for losses. Employing a normative legal approach, this research analyzes applicable laws, regulations, and case studies, particularly judicial decisions involving disputes between passengers and international airlines. The findings indicate that legal, administrative, technical, and economic barriers constitute significant obstacles for passengers seeking compensation. The study underscores the need to re-evaluate the principle of limitation of liability, enhance cabin security standards, and strengthen consumer dispute resolution mechanisms to establish a more equitable and effective system of protection.